Analisis kesulitan belajar siswa SMA pada pembelajaran geometri - Sari, Rika Mulyati Mustika; Roesdiana, Lessa (Universitas PGRI Semarang, 2019)
Geometry is one branch of mathematics for high school level, one of which is cone slices which deal with circles, ellipses, parabola, and hyperbole. However, from the data obtained in the last few years from the PUSPENDIK the value of the students' mathematics at the Geometry branch is always lower than the other branches of the mathematics branch. This is what encourages researchers to conduct preliminary research that aims to analyze and describe student learning difficulties in learning geometry. The benefits of this research are a reference for research to develop appropriate mathematics teaching materials and in accordance with the characteristics of geometry. This research use desciptive qualitative approach. Methods of data collection are observation, interviews and questionnaires. Analysis of the data used is using the Miles and Huberman models which include: data reduction, data display, and conclusion drawing / verification. The results of this study are in the form of a description of learning difficulties faced by students in learning geometry. Â Keywords: learning difficulties, GeometryÂ